Penerapan Model Discovery Learning Berbasis Assessment For Learning Untuk Meningkatkan Hasil Belajar Ipa, Sikap Ilmiah, Dan Respon Siswa Kelas VIII B Semester Genap Smp Negeri 1 Manggis - I Ketut Hariawan (Cetta: Jurnal Ilmu Pendidikan, 2019)
This action research aims: (1) to improve the science learning outcomes of VIIIB graders in the middle semester of SMP Negeri 1 Manggis in the 2015/2016 academic year by applying discovery learning models based on assessment for learning, (2) to improve the scientific attitude of VIIIB graders in the even semester Negeri 1 Manggis 2015/2016 academic year with the application of discovery learning models based on assessment for learning, (3) to determine the response of class VIIIB students of SMP Negeri 1 Manggis after the implementation of discovery learning models based on assessment for learning. This type of research is classroom action research. The subjects of this study were 30th grade VIIIB students, and the objects of this study were science learning outcomes, scientific attitudes, and student responses. This action research is planned to be carried out in two cycles. Learning outcomes data were collected using multiple choice tests, scientific attitude questionnaires, and student response questionnaires. Data were analyzed by descriptive analysis. The results of the study showed that: (1) the VIIIB grade science learning outcomes in the even semester increased in the first cycle by an average of 71.80 with a gradeical completeness of 80%, and the second cycle averaging 75.0 with a gradeical completeness of 90% ; (2) The scientific attitude of grade VIIIB students even experienced an increase in the first cycle of an average of 70.7 in the good category, and in the second cycle the average of 78.97 was in good qualification. (3) the response of students in cycle 2 an average of 75.97 is in the good category. With the achievement of the average learning outcomes of science 75.0, it means that the level of success has been set, which is 70, so that the action is considered successful. Scientific attitudes and student responses are in the good category. Thus it can be said that the application of the discovery learning model based on assessment for learning can improve science learning outcomes, scientific attitudes, and responses of VIIIB grade students even in the mangosteen junior high school year 2015/2016.